Ekstrak turi, Koloni Bakteri PENGARUH EKSTRAK DAUN TURI MERAH TERHADAP KOLONI BAKTERI PADA MENCIT NIFAS - Tut Rayani Aksohini W (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2018)
Abstract The incidence of infection often occurs during the puerperium period triggered by an injury to the reproductive organs. This triggers the emergence of pathogenic bacteria through the birth canal such as Streptococcus agalactiae. Turi (Sesbania grandiflora) is a very easy plant to grow often used in medicine because it has chemical content such as flovonoids, saponins, tannins, carbohydrates, phytosterol, triterpenes. The type of research method to be used is true experiment posttest only control group design. Research replication of 28 mice and grouped into 4, control, P1 group, group P2 and group P3. The measurement of bacterial colonies was done using the Pour Plate method. The results of the analysis as a whole showed that the extract of red turi leaves was able to decrease the bacterial colonies in the puerperal mice. Provision of red turi leaf extract in puerperal mice did not significantly influence bacterial colonies. Therefore, red turi leaf extract can be useful to improve body immunity to avoid infection during childbirth period. Keywords: red turi (Sesbania grandiflora)leaf extract, bacterial colonies